A serial case of Japanese encephalitis in West Kalimantan - Thedra, Nathania; Phangkawira, Evelyn (Indonesian Pediatric Society, 2024)
Japanese encephalitis (JE) is an important, vaccine-preventable cause of viral encephalitis in Asia. This medical condition has a high morbidity and mortality rate, remains an under-recognized cause of encephalitis, with high rate of mortality and severe sequelae in children, especially in West Kalimantan. However, poor surveillance has made the burden difficult to quantify, hindering decisions about subsidized vaccine introduction. In this serial case, the most common clinical presentations of JE were fever, altered mental status, seizures, vomiting, and positive meningeal irritation signs or pathologic reflexes. The JE mortality rate was as high as 40%. These highlight the need of disease surveillance, diagnostic kits supply, and health education to increase public disease awareness.